Nawagaka: Cut Coins to Leave a Trace: Contemporary Scenic Baroque Practices - Vizcaíno Martínez, Juan Manuel (2025)
This article aims to problematize the exercise of Nawagaka, a performance action presented at the Encuentro Internacional de Performance “No lo Haga Usted Mismo” (NHUM) on December 1, 2022, during the day of activations in the central plaza of the municipality of Aguascalientes, Mexico. From its conceptualization and preparations, this participation was executed in several organic moments that are presented —in a report format— for the gradual and critical problematization of its context of emergence and execution, based on an explanatory scheme that argues that the intersection of modernity-capitalism-colonialism is a tautological system of existence integrated and determining our identities and territories of existence. In this context, the faculties of production of “plastic images” are identified as correlates of existence, opening an analogous bridge between social reality and theater as an experience —also social— that allows us to conceptualize the idea of a ??“theater of existence”. In this scenario, the process of metamorphosis of a sequence of figures —anarchist and baroque— will unfold, giving rise to the Nawagaka as a liminal character in this proposal of social theatrical performance. Thus, we will carefully analyze each of the moments, actions and interactions —in crossroads with their theoretical and methodological implications— during the participation in the NHUM. The discussion between anarchoindividualisms, post-structuralisms, baroque studies, criticism of modern colonialisms and classical and contemporary communisms, applied to the analysis of the Nawagaka case study, proposes the practical idea of ??an imaginative materialism in the celebration of a possible scenic anarchism that preserves and actively exercises the emancipatory forces of situated psychosocial and socioterritorial production.